2022
DOI: 10.1002/jnr.25056
|View full text |Cite
|
Sign up to set email alerts
|

What does gender has to do with math? Complex questions require complex answers

Abstract: Whether mathematics is a gendered domain or not is a long‐lasting issue bringing along major social and educational implications. The females' underrepresentation in science, technology, engineering, and mathematics (STEM) has been considered one of the key signs of the math gender gap, although the current view largely attributes the origin of this phenomenon to sociocultural factors. Indeed, recent approaches to math gender differences reached the universal conclusion that nature and nurture exert reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 114 publications
(169 reference statements)
0
11
0
Order By: Relevance
“…Researchers have offered two main explanations to the emergence of gender differences in STEM. The first explanation maintains that the gender gap originates from (innate) sex-differences in the cognitive abilities underpinning performance in STEM (Halpern and LaMay, 2000 ; Miller and Halpern, 2014 ; Girelli, 2022 ). Sex-related differences in cognitive abilities underpinning performance in STEM are indeed reported in some studies (Halpern and LaMay, 2000 ; Maloney et al, 2012 ; Miller and Halpern, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have offered two main explanations to the emergence of gender differences in STEM. The first explanation maintains that the gender gap originates from (innate) sex-differences in the cognitive abilities underpinning performance in STEM (Halpern and LaMay, 2000 ; Miller and Halpern, 2014 ; Girelli, 2022 ). Sex-related differences in cognitive abilities underpinning performance in STEM are indeed reported in some studies (Halpern and LaMay, 2000 ; Maloney et al, 2012 ; Miller and Halpern, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These gender disparities can determine differences in students' achievements (Maloney et al, 2012 ) and consequently affect motivation for the pursuit of studies and careers in STEM (Wang and Degol, 2017 ). The second explanation has it that the gender gap originates from sociocultural factors, such as inequalities in the social and educational systems, and gender role stereotypes that determine explicit and implicit biases of boys and girls in how they perceive and evaluate their and others' performance and abilities in STEM (Charlesworth and Banaji, 2019 ; Girelli, 2022 ). For instance, exposure to role models, prior experiences with STEM and the expectations of others (e.g., parents) can contribute to the emergence of biased explicit and implicit (i.e., less conscious) beliefs on boys and girls abilities in STEM, which can influence individuals' behaviors, performance and learning experience (Miller and Halpern, 2014 ; Flore and Wicherts, 2015 ; Master et al, 2017 ; Charlesworth and Banaji, 2019 ), with possible long-lasting effects on girls' motivation to pursue studies or careers in the STEM domain (Charlesworth and Banaji, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on information literacy, boys have shown higher scores when assessing their own capabilities (Taylor and Dalal, 2017). This may be related to the persistent societal trend in the USA of boys being seen as more capable and interested in anything related to STEM (Girelli, 2023; Kurtz-Costes et al , 2008). In addition, males remain the predominant participants or fans of hobbies, such as console video games, and sports, such as baseball, that involve comprehending, tracking and analyzing various data points to compare and contrast players (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…STEM stereotypes are present in several niches in society, not only in academic environments. From offensive jokes to controversial studies, women are raised to believe women lack STEM ability when compared to men because of biological differences (i.e., brain anatomy, hormones), but none of them was proven ( Girelli, 2023 ). This existing stereotyped STEM male model is replicated through generations of parents and/or educators ( Tomasetto et al, 2011 ).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%